2015
DOI: 10.4293/jsls.2014.00251
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Outpatient Total Laparoscopic Hysterectomy

Abstract: Background and Objective:Ambulatory total laparoscopic hysterectomy (TLH) could lead to significant cost savings, but some fear the effects of what could be premature postsurgical discharge. We sought to estimate the feasibility and safety of TLH as an outpatient procedure for benign gynecologic conditions.Methods:We report a prospective, consecutive case series of 128 outpatient TLHs performed for benign gynecologic conditions in a tertiary care center.Results:Of the 295 women scheduled for a TLH, 151 (51%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 23 publications
1
41
0
3
Order By: Relevance
“…These patients experienced more pain and were more dissatisfied, and the number may correspond to clinical reality when LH is routinely performed as an outpatient procedure in settings where treatment is free of cost for the patient. As expected, we found no difference in complication and readmission rates, in agreement with previous studies on outpatient TLH . The complication rate at 12% is equivalent to the national level in Denmark .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These patients experienced more pain and were more dissatisfied, and the number may correspond to clinical reality when LH is routinely performed as an outpatient procedure in settings where treatment is free of cost for the patient. As expected, we found no difference in complication and readmission rates, in agreement with previous studies on outpatient TLH . The complication rate at 12% is equivalent to the national level in Denmark .…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge this is the first RCT examining patient satisfaction in patients undergoing outpatient TLH as a routine. In selected women, outpatient TLH was associated with same‐day discharge rates between 85% and 100% . Studies investigating predictors and rates of readmissions after outpatient LH found same‐day discharge rates between 20% and 34% after TLH .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations